A Compact Embodiment of Pluralities and Denial of Origins: Atwood’s The Year of The Flood - Sağıroğlu, Rana (European Journal of Multidisciplinary Studies, 2016)
Margaret Atwood, one of the most spectacular authors of postmodern movement, achieved to unite debatable and in demand critical points of 21st century such as science fiction, postmodernism and ecocriticism in the novel The Year of The Flood written in 2009. The novel could be regarded as an ecocritical manifesto and a dystopic mirror against today’s degenerated world, tending to a superficial base to keep the already order in use, by moving away from the fundamental solution of all humanity: nature. Although Atwood does not want her works to be called science fiction, it is obvious that science fiction plays an introductory role and gives the novel a ground explaining all ‘why’ questions of the novel. However, Atwood is not unjust while claiming that her works are not science fiction because of the inevitable rapid change of 21st century world becoming addicted to technology, especially Internet. It is easily observed by the reader that what she fictionalises throughout the novel is quite close to possibility, and the world may witness in the near future what she creates in the novel as science fiction. Additionally, postmodernism serves to the novel as the answerer of ‘how’ questions: How the world embraces pluralities, how heterogeneous social order is needed, and how impossible to run the world by dichotomies of patriarchal social order anymore. And lastly, ecocriticism gives the answers of ‘why’ questions of the novel: Why humanity is in chaos, why humanity has organized the world according to its own needs as if there were no living creatures apart from humanity. Therefore, The Year of The Flood meets the reader as a compact embodiment of science fiction, postmodernism and ecocriticism not only with its theme, but also with its narrative techniques.